Factors associated to suicidal attempt among medical students of a private university in Lima - Sindeev, Andrey (2020)
Objectives: To determine the prevalence of and risk factors for suicidal attempts among first year medical students of a private university in Lima. Methods: A cross-sectional study was carried out including 134 (98.5% of the total number of students) first year medical students of Universidad Privada Norbert Wiener (Lima, Perú) who consented to participate in the study. A bivariate analysis was carried-out (p<0.05). Results: the prevalence of life time suicidal attempt, wish to die and suicidal attempt was 34.3%, 22.4% and 19.4%. The suicidal risk was 32.1%. Bivariate analysis identified severe family dysfunctionality (p<0.001); probable depression (p<0.001), on the other hand the suicidal attempt was associated with probable depression (p<0.05), anxiety (p<0.05), homicidal thinking (p<0.001), violence risk (p=0.005), severe family dysfunctionality and alcohol drinking suspicion (p<0.05). Conclusions: First year medical students at Universidad Privada Norbert Wiener (Lima, Perú) are at risk of suicidal attempts, which is associated to other mental health problems.